Conquering Stress in Times of Pandemic: An Intervention Study to Manage Stress among College Students - Botabara-Yap, Mary Jane; Rodriguez, Princess Red Rose G. (8ISC Abstract Proceedings, 2022)
The COVID-19 pandemic has brought many challenges throughout the population spectrum. The sudden shift of classes from face-to-face to fully online classes has brought into the spotlight the mental health issue of various groups, including college students. The aim of this study was to determine the effect of a stress management program on perceived stress, knowledge, attitude, and preventive practices among college students in the Adventist University of the Philippines. The study utilized a pre-test/post-test quasi-experimental design among 40 participants through random sampling. The intervention program was conducted from March 6 until April 17, 2021, and consisted of motivational talks, lectures, focused group discussions, testimonials, and support groups. Descriptive (mean and percentage) and inferential (paired t-test) statistics were used to analyze the data. Both groups showed moderate stress, very good knowledge, negative attitude, and good preventive practices pre and post-intervention. There is no significant difference in both groups prior to the program; however, it showed a significant difference in the perceived stress scale, which strongly indicates that the stress level of the participants decreased after the stress management program. Moreover, the attitude and practice gain scores of the participants were higher, while the gain score for perceived stress was lower in the experimental group. Further, preventive practices showed a significant difference in the gain score as compared to knowledge and attitude. Results showed that the stress management program was a success and is recommended to be done regularly for college students. Keywords : academic stress, stress management program, pandemic, perceived stress scale